2014
DOI: 10.1089/omi.2013.0131
|View full text |Cite
|
Sign up to set email alerts
|

How Does Mother-to-Child Transmission of HIV Differ Among African Populations? Lessons fromMBL2Genetic Variation in Zimbabweans

Abstract: Mannose binding lectin (MBL) is a pathogen pattern recognition protein involved in antimicrobial activities. Variation in MBL2 gene has been extensively implicated in differential outcomes of infectious diseases in studies conducted outside Africa, but virtually very little is known on the role of this candidate gene in the African continent. We investigated human genetic variations in MBL2 in a Zimbabwean pediatric population and their putative associations with HIV infection in perinatally exposed children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…According to the findings of this study, it is highly probable that the black South African population share very few common variants associated with T2D with other ethnic groups. This study supports what has been reported in a number of local genetics studies in Southern Africa, namely that the genetic background of black South Africans is diverse and cannot be extrapolated using genetic variants from other ethnicities (Bosch et al 2014;Dandara et al 2014;May et al, 2013;Mhandire et al, 2014). Therefore the results of this study highlight the need for population-specific variants to evaluate T2D genetic susceptibility in the black South African population.…”
Section: Conclusion and Forward Looksupporting
confidence: 88%
“…According to the findings of this study, it is highly probable that the black South African population share very few common variants associated with T2D with other ethnic groups. This study supports what has been reported in a number of local genetics studies in Southern Africa, namely that the genetic background of black South Africans is diverse and cannot be extrapolated using genetic variants from other ethnicities (Bosch et al 2014;Dandara et al 2014;May et al, 2013;Mhandire et al, 2014). Therefore the results of this study highlight the need for population-specific variants to evaluate T2D genetic susceptibility in the black South African population.…”
Section: Conclusion and Forward Looksupporting
confidence: 88%
“…Sub-Saharan Africa has a high burden of viral [ 26 – 28 ], bacterial [ 27 – 29 ] and parasitic infections [ 12 , 13 , 27 ]. Assessment of polymorphisms in the MBL2 gene and promoter region to determine functional MBL deficiency has been carried out in different populations with few studies in Sub-Saharan Africa [ 17 , 30 , 31 ]. Schistosomes carry sugar molecules or glycoconjugates on the surface of all their developmental stages [ 32 , 33 ] and these glycoconjugates interact with innate immune recognition molecules including MBL [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their collective contribution to gene expression or overall protein structure may be important, as we have shown with other genes. [10,[13][14][15] In an effort to understand the combinational effect of APOBEC3G polymorphism on HIV transmission haplotype, frequencies were compared between HIV-infected and uninfected groups of children. LD was generally strong between pairs of the APOBEC3G SNPs studied in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from the Better Health for the African Mother and Child (BHAMC) cohort, a longitudinal study of mother-child pairs followed up between 2002 and 2012, as described elsewhere. [10] In summary, the participants were 104 unrelated children aged 7 to 9 years, of bantu African origin. These included 32 children perinatally infected with HIV (EI) who were available in the cohort at the time of collection, and 72 healthy HIV-uninfected children comprising 36 exposed to HIV in utero but not infected (EU) and 36 unexposed and uninfected (UEUI).…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation